The association of the step duration in an incremental protocol in the rower ergometer and the maximal lactate steady state intensity - Fraga, Pedro (2023)
This study aims to analyse which are better step duration related to the maximum lactate steady-state test (MLSS) intensity and the intensity equivalent to the accumulation of 4mmol/L lactate (AnT4) determined through an incremental protocol using a rowing ergometer, using different steps durations (step3min, step5min, step7min). Ten elite Portuguese rowers (25.1 ± 4.82 years; 177.5 ± 5.50 cm; 69.8 ± 2.74 kg) performed rowing ergometer protocols to determine the maximum lactate steady state (MLSS). Subsequently, incremental tests were realised to determine AnT4, using different step durations (step3min, step5min, step7min). The results showed a strong correlation between MLSS and AnT4 (r>0.90; p<0.001) obtained AnT different steps (step3min, step5min, step7min). However, the determined intensity equivalent to 4mmol/L obtained with different step durations that showed the highest correlation with MLSS (246.5 ± 35.20W) was verified in the protocol of 7minute steps (251.5 ± 35,72W). The present study indicates that the use of 7 minutes steps is the most appropriate for determining the AnT4 intensity related to the aerobic component of a high-performance rowing athlete.